Inovasi Limbah Cair Singkong Menjadi Nata de Cassava Sebagai Bisnis Kuliner - Amaliya Sita Permatasari; Ima Winaningsih; Jamal Adi Prasetiyo (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2019)
Cellulose bacterial is cellulose formed by bacteria sugar content in waste. Cassava-based industrial liquid waste contains sugar (5-7)%, so it has the potential as a substrate because it meets the minimum glucose requirements of (6-7)% to form cellulose bacterial. The waste was obtained from liquid waste from home industry cassava rengginang in Nyamok Village. However, liquid waste smells bad because it is directly streamed into the environment. Therefore, the purpose of this activity is to give solutions for overcome environmental pollution and increase the income of cassava rengginang craftsmen in Nyamok Village. The methods are lectures, demonstrations, production training, assistance, and socialization. Liquid waste made from cassava chips was used as raw material for making nata de cassava. It was fermented with Symbiotic Culture of Bacteria and Yeast (SCOBY) bacteria for 10-14 days. Training activities were successful as 86% people participated in the training. The participants were around 40 years old and elementary school graduates. The characteristics of the participants influence their interest and ability to absorb new information. It is proved by 89% of the participants are able to make Nata de cassava and their understanding of the counseling material was above the target of 80%.Keywords: cassava rengginang; nata de cassava; production training; SCOBY.